Droughts, women and indigenous people in Chile: Assessing the impacts on income and employment - Rodrigo Pérez Silva; Mayarí Castillo; Chiara Cazzuffi (Inter-American Development Bank (IDB), 2023)
Climate change is a pressing issue, affecting the lives of all people across the world. However, poorer and excluded communities are usually more affected, especially in low-income countries. Among them, women but particularly indigenous groups in rural areas seem to bear the bulk of the impacts produced by climate change and its many manifestations. We study the relationship between droughts and incomes and labor market outcomes in Chile over the period 1990-2017, focusing in particular on indigenous women. Our results show that overall indigenous women are the group most severely affected by droughts, decreasing their income, their probability of working in agriculture, and increasing their likelihood of working as an unpaid family worker or being out of the labor force. Results are robust to the use of different variables to measure droughts and to different econometric specifications. Our study corroborates the existence of marked heterogenous effects of climate change on different population groups and the vulnerability of indigenous communities to these shocks.
Keywords: E24; I31; J16; Q54; 330; Droughts; Climate change; Women; Indigenous groups; Water scarcity; Chile